FEARLESS WOMAN-PILOT WITH FAIR LOVE TO A BEAUTY - I.V. DRYAGINA - V.F. Pivovarov; P.F. Kononkov; G.D. Levko; L.U. Kan (Овощи России, 2011)
On 31st March, 90th birth and 50 years of working, scientific, pedagogical activities of renowned scientist in plant genetics, fruit-tree genetics, breeding and seed production of flowers, doctor in agriculture, head of laboratory of breeding and seed production of flowers at All-Russian Research Institute of Vegetable Breeding and Seed Production (1978-1996) Irina Victorovna Dryagina is celebrating her anniversary.